'I think we are going to leave these cases'. Obstacles to surgery in rural Malawi: a qualitative study of provider perspectives. Issue 10 (29th August 2018) - Gajewski, J.; Bijlmakers, L.; Mwapasa, G.; Borgstein, E.; Pittalis, C.; Brugha, R.
Abstract: Objectives: Surgical services at district level in Malawi are poor, yet the majority of the population resides in rural areas. This study aimed to explore the perceived obstacles to surgery from the perspective of the cadre directly responsible for surgical service delivery at district hospitals. Methods: Qualitative interviews were conducted with 16 clinical officers (COs) receiving surgical training in eight public district hospitals and their 12 trainers. Thematic analysis of data was conducted using a top‐down coding method. Results: Despite readiness of the COs to conduct operations, other staff essential for surgery were sometimes unavailable to support them. Respondents attributed this to lack of skills, weak motivation or poor work ethic of their colleagues. Lack of commitment to do surgery, passiveness, lack of initiative in problem‐solving and 'laziness' of surgical team members were among the reasons provided by study participants, accounting for unnecessary cancellations of elective surgery and inappropriate referrals of emergency cases. Other factors included infrastructure breakdowns and stock‐outs of surgical supplies. There were instances where COs, and their supervisors, showed initiative in finding solutions to problems resulting from poor district hospital management practices. Conclusions: This study demonstrates how the motivation of surgical team members is a key factor in deciding whether or not to perform operations; and that shortages of supplies or infrastructure need not be an absolute obstacle to service delivery. Scale‐up of surgical services at district level requires investments to improve surgical and anaesthetic skills, to strengthen human resources and facility management, and to ensure the availability of reliable infrastructure and essential supplies.